Analysis of irrigation network condition On Cipamarangan Irrigation system, Sukabumi Regency - Liana Anifa; Arham Ajrul; Maulana M. Rizki; Sari Nita Kurnita (BIO Web of Conferences)
Irrigation networks have important role to support agricultural productivity and farmers welfare. The decline in the condition and function of irrigation networks can lead to disruption in the distribution of water in irrigation areas. This occurs due to several things such as sedimentation, weed growth, corrosion of the floodgates and leaks in the channel walls. This study aims to evaluate the physical condition and functioning of irrigation networks based on field surveys and available technical data. The method used in this research is by identifying the condition and functioning based on indicators of structures, floodgates and measuring buildings. Assessment of the condition and functioning of each irrigation asset according to Peraturan Menteri Pekerjaan Umum dan Pe-rumahan Rakyat (PUPR) of 2015 and Kriteria Perencanaan Bagian Bangunan of 2013. The results showed that the condition of the Cipamarangan irrigation network was classified as not good with an index of 1.5 and its functioning was classified as not functioning with a percentage of 31%. Recommended actions are suggested to do heavy repairs or replacements on the irrigation network DI. Cipamarangan. In addition, the implementation of monitoring technology and community in-volvement in maintenance were identified as important steps to ensure the sustainability and opti- mization of irrigation networks.